Wanting Sheila dead [large type] : - Haddam, Jane, 1951-2019- (Haddam, Jane, 1951-2019- Gregor Demarkian books, 2011)
Sheila Dunham is a gossip columnist's dream - she is famous, loud, and, to almost everyone who has met or seen her, deeply, spectacularly offensive. Fired from every TV job she's ever had, she's now producing and hosting her own reality show, where thousands of women compete for a spot in the house where it will be filmed. On the first day of shooting, though, someone fires a gun at - and misses - Sheila Dunham